Places, rituals and past worlds: encounters on a Tibetan pilgrimage in North India - Schröder, Nike-Ann (Ritual journeys in South Asia, 2019)
This chapter presents a thick description of a pilgrimage of a group of Tibetan refugees from Ladakh across the Himalayas to Rewalsar. The